Faktor-Faktor Yang Mempengaruhi Kinerja Perusahaan Consumer Non-Cyclicals Sebelum dan Pada Masa Covid-19 - Mayo, Ignatius Flora De; Yanti (Jurnal Paradigma Akuntansi, 2025)
This research was conducted to find out how the influence of liquidity, leverage, company size, and growth on firm performance in non-cyclical sector companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. This study uses 29 non-cyclicals sector companies as a sample for 2018-2019 which represents the pre-pandemic period and 2020-2021 which represents the period during the Covid-19 pandemic. Data processing techniques using purposive random sampling method and multiple regression analysis and Wilcoxon signed rank test with SPSS. The result of this study indicate that liquidity, company size, sales growth had a significant positive effect and leverage had no effect on company performance before the pandemic, whereas during the pandemic the liquidity variable, company size had a significant positive effect and the leverage and sales growth variables had no effect on company performance. This study found no significant difference between the average company performance before and during the Covid-19 pandemic. The implication of this study is the need to increase liquidity and size in order to improve company performance and provide a positive signal to investors.